Prediction rule for estimating advanced colorectal neoplasm risk in average-risk populations in southern Jiangsu Province - Chen, Guochang; Mao, Boneng; Pan, Qi; Liu, Qian; Xu, Xinfang; Ning, Yueji (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Objective: The aim of this study was to establish the risk scoring system towards the advanced colorectal neoplasm (CN) risk in the average-risk populations in the southern Jiangsu Province, and to evaluate the screening efficacy. Methods: Totally 905 cases of the average-risk populations who received the colonoscopy were selected as the objective. The multivariate logistic regression analysis method was used to establish the scoring system towards the occurrence risk of the advanced tumor, and its screening efficacy was evaluated through the prediction consistency, distinguishing ability and screening accuracy. Results: The scoring system consisted of five variables, namely age, gender, coronary heart disease, egg intake and stool frequency. The results revealed that it had good prediction consistency (P=0.205) and distinguishing ability [the area under the receiver operating characteristic (ROC) curve was 0.75, with 95% confidence interval (95% CI) of 0.69-0.82]. Thus, 2.5 points was set as the screening cutoff value, and its sensitivity, specificity, accuracy, positive predictive value, negative predictive value, positive likelihood ratio and negative likelihood ratio were 93.8 %, 47.6%, 50.1%, 9.1%, 99.3%, 1.79 and 0.13, respectively. Conclusions: The established scoring system had good screening efficacy, and can be used as the screening tool applying to the CN screening within the average-risk populations in the southern Jiangsu Province.